Effects of exercise-based cardiac rehabilitation in patients with acute coronary syndrome aged 80 years and older. (25th November 2020) - Back, M; Brosved, M; Albertsson, P; Karlsson, T; Philip Wigh, J; Sundberg, H; Ziden, L; Hirlekar, G
Abstract: Background: The beneficial effects of exercise-based cardiac rehabilitation (exCR) in patients with acute coronary syndromes (ACS) are well known. Patients aged 80+ have, however, been underrepresented in randomized controlled trials. Purpose: The primary aim was to evaluate effects of exCR in patients with ACS 80+ in terms of maximum aerobic capacity, compared with a control group. Secondary aims were to evaluate effects of exCR between groups regarding muscular endurance, submaximal aerobic capacity, physical function and self-reported health. Methods: A total of 26 patients (58% men), with ACS, median age 82.5 (25th-75th percentiles, 81–84) years, were included at a university hospital. Patients were randomized to hospital-based exCR, including aerobic, resistance- and balance exercises 2 times/week and a home-based exercise program 1 time/week or to a control group (C-group) for 4 months. We report differences in changes (0–4 months) between the groups regarding maximum aerobic capacity (exercise ECG), 6MWT, muscle endurance tests (shoulder flexion and heel-lifts), timed-up and go (TUG), Short Physical Performance Battery (SPPB), one leg stand test and self-reported health (one item question). T-tests, Mann-Whitney U tests and Chi2-tests were used as appropriate to describe differences between groups. Results: There were no significant differences between groups at baseline, except for age with the exCR-group being older. At 4 months, we found no significant differences between the groups in maximum aerobic capacity. However, the exCR-group significantly improved their 6-min walking distance more, with a median of 39 m (17–57.5), compared to 16.5 m (−15.5–33) in the C-group, p=0.04. In addition, the exCR-group significantly improved in muscle endurance (maximum reps) while the C-group declined; heel-lift right, mean 2.3±3.8 vs −1.6±4.5, p=0.04 and left, mean 2.9±3.9 vs −4.6±4.6, p=0.001, shoulder flexion mean 5.5±4.5 vs −3.1±3.1, p≤0.001. Moreover, the exCR-group significantly improved their physical function in terms of SPPB total score with in median 1.5 (1–2) points, compared to 0 (−1–1) in the C-group, p=0.02 and one leg stand test 1.5 (0–2) points, compared to a decline with −0.5 (−2–0) points in the C-group, p<0.001. There were no significant differences between groups in shoulder abduction, TUG and self-reported health. Conclusions: We report introductory results that patients with ACS, aged 80+, participating in an exCR program can improve walking distance, muscle endurance and physical function, however not maximum aerobic capacity. Therefore, we encourage an increased referral to exCR of this increasing group of patients to potentially enable more elderly to preserve mobility and independence in their daily living. These results must, however, be confirmed in larger studies. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): The Swedish Heart- and Lung Association